CUG‐binding protein 1 (CUGBP1) expression and prognosis of brain metastases from non‐small cell lung cancer. Issue 1 (21st May 2015) - Wang, Xiaofei; Jiao, Wenjie; Zhao, Yandong; Zhang, Liangdong; Yao, Ruyong; Wang, Yongjie; Wang, Mingzhao; Luo, Yiren; Zhao, Jinpeng
Abstract: Background: The brain is a frequent site of metastases from non‐small cell lung cancer (NSCLC). The purpose of this study was to detect the expression of CUG‐binding protein 1 (CUGBP1) messenger ribonucleic acid (mRNA) and Ki‐67 in metastasized brain tissue from NSCLC and determine the relationship between CUGBP1 and brain metastases. Methods: The expression of CUGBP1 mRNA and Ki‐67 in metastasized brain tissue from NSCLC was investigated by semiquantitative polymerase chain reaction and immunohistochemistry, respectively. The expression of CUGBP1 and Ki‐67 in metastasized brain tissue from NSCLC was related to clinical characteristics, as assessed using the chi‐square test. The prognostic significance was assessed by univariate and multivariate analyses using the Cox hazard model. Results: The expression of CUGBP1 mRNA and Ki‐67 was overexpressed in metastasized brain tissue from NSCLC and was correlated with differentiation. In addition, by both univariate and multivariate survival analyses, CUGBP1 expression, Ki‐67 expression, and age were noted to be independent indicators of a shorter postsurgical survival. Conclusion: The expression of CUGBP1 is an important factor in the development of brain metastases from NSCLC.